THE IMPACT OF SOCIAL CLASS IN JANE AUSTEN PERSUASION - Pinontoan, Livia Karina; Oroh, Elisabeth Z.; Kamagi, Sarah (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this research is to reveal the impact of social class reflected in Jane Austen’s Persuasion. The writer used the qualitative method because this research analyzed and collects data from the novel by the type of characters, the story, and the social class that occurs in the novel. In analyzing the data the writer used mimetic theory, the data were collected in the novel Persuasion by Jane Austen, the writer read the novel and identified the characters, the story that related to social class that occurs in the novel, to support this research the writer used several books, journal, and web pages. The novel tells about social class in the Victorian era, where class and status affect someone’s life. Social class is a group of people that share similar status, occupation, and wealthiness. This novel tells about a couple that was separated because of the social status differences, where Captain Wentworth is a man with unstable finances, while Anne Elliot is a woman from the upperclass social status. They were separated because of the persuasion of Lady Russel which causes Sir Walter Elliot which is Anne’s father to separate them. Sir Walter Elliot is a hedonist which ends him in bankruptcy. The result of the finding is that social class has an impact on human life and society. Social class differences affect many aspects ranging from lifestyle, life chances, and inequality of social status.